Pengaruh Suhu Pemanasan dan Lama Pemanasan Terhadap Kandungan Vitamin C Beberapa Varietas Nanas - Indah Rizka (Herbal Medicine Journal, 2019)
Pineapple (Ananas comosus L.) is a type of tropical plant originating from Brazil, Bolivia and Paraguay. This plant is included in the pineapple-nanasan family (Family Bromeliaceae). The plant is of low stature, with 30 or more long, sharp-tipped leaves arranged in a rosette around a thick stem. Vitamin C or L-ascorbic acid, or ascorbate is an essential nutrient for humans and animals. Vitamin C from nature is commonly found in fruits or vegetables. Examples of local fruits known to be rich in vitamin C are local lemons, limes, guavas, poor apples and pineapples. The purpose of this study was to determine whether the heating temperature had an effect on the vitamin C content in pineapple juice, to determine whether the heating time had an effect on the vitamin C content in pineapple juice. This research was carried out using the ultraviolet spectrophotometric method.The highest vitamin C content in pineapple, namely light green pineapple juice, is higher than honey pineapple juice and regular pineapple juice. Light green pineapple juice with a temperature of 80 ° C in the 60th minute shows a concentration of 9,00529 compared to honey pineapple juice with a concentration of 8,75580 and regular pineapple juice with a concentration of 4,25629. The results of research on vitamin C showed that heating times of 15 minutes, 30 minutes, 45 minutes, and 60 minutes caused a decrease in the vitamin C content of pineapple juice. The results showed that the higher the temperature and duration of heating, the lower the vitamin C produced during heating and using high temperatures would also damage the vitamin C concentration.